Carer Experience Supporting Someone With Dementia and Cancer: A Narrative Approach. (April 2018) - Witham, Gary; Haigh, Carol; Mitchell, Duncan; Beddow, Anna
In this article, we examine the challenges of informal carers supporting someone with dementia and cancer within the United Kingdom. Interviews were conducted with seven informal carers using a narrative approach to examine the construction of their experiences. Our findings demonstrate how informal carers navigate a path through complex cancer treatments and support their relative. A cancer diagnosis often requires multiple treatment visits to an oncology center, and this can be challenging for carers. They find that they need to coordinate and manage both health professionals and their relative in terms of getting access to appropriate services and support. This process can be particularly challenging in the presence of a cognitive impairment that often demands effective communication with different agencies. Carers frequently experienced multiple challenges including dealing with the stigma that is characteristic of the dementia experience and the added complexity of negotiating this within a cancer care context.